The influence of sediment properties and experimental variables on the efficiency of electrodialytic removal of metals from sediment - Pedersen, Kristine Bondo; Lejon, Tore; Jensen, Pernille E.; Ottosen, Lisbeth M. (Journal of Environmental Chemical Engineering, 2017)
Accepted manuscript version. Published version available at https://doi.org/10.1016/j.jece.2017.10.031 . Accepted manuscript version, licensed CC BY-NC-ND 4.0. Chemometrics was used to determine the influence of sediment properties and experimental settings for the electrodialytic removal (EDR) of Cu, Pb and Zn from six harbour sediments from Greenland and Norway. A Projection onto latent structures (PLS) model revealed that the most important sediment properties for achieving acidification (lag-phase, pH > 4), necessary for desorbing and mobilising metals in the polluted sediments, were buffer capacity and grain size distribution. Higher stirring rate reduced the acidification time, stressing the importance of thorough mixing of the sediment suspension to achieve a fast and uniform acidification. PLS models were calculated to determine the influence of sediment properties on the removal of metals during EDR, which was observed to vary depending on the targeted metal and the stage of the remediation. In general, buffer capacity, grain size distribution, element composition and metal partitioning were important for remediation efficiency and are important parameters for determining optimal experimental settings. In the fast removal phase (final pH 2–4), organic matter as well as stirring rate had increasing importance indicating oxidation and release of metals at this stage. Understanding the influence of sediment properties is important for determining experimental settings in accordance with the phase of EDR.